Growth modelling and analysis of microalgae cultivation in photo-bioreactor - Wong, Yih Han (Curtin University, 2014)
Design of Experiments was applied in this study to identify the effects of interaction between environmental conditions on Chlorella vulgaris growth in flat panel photo-bioreactors. Three mathematical regression models were developed to illustrate growth rate, biomass productivity and lipid productivity. The optimum lipid productivity of 1.75 mg/L•day was obtained under optimized process setting of 5 g/L bicarbonate concentration, 0.97 g/L nitrate concentration and light irradiance of 4500 LUX.